2002
DOI: 10.1377/hlthaff.21.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Policy Implications Of The Gradient Of Health And Wealth

Abstract: Men in the United States with family incomes in the top 5 percent of the distribution in 1980 had about 25 percent longer to live than did those in the bottom 5 percent. Proportional increases in income are associated with equal proportional decreases in mortality throughout the income distribution. I discuss possible reasons for this gradient and ask whether it calls for the redistribution of income in the interest of public health. I argue that the existence of the gradient strengthens the case for income re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
304
1
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(330 citation statements)
references
References 31 publications
12
304
1
13
Order By: Relevance
“…A large literature shows that those of low socio-economic status are characterized by worse health than their better-off counterparts and that differences in health often originate in childhood and even earlier, in the newborn period (see Case, Paxson and Lubotsky, 2002; Deaton, 2002; Cutler, Deaton and Lleras-Muney, 2006 and references therein). Explanations of the gradient include differences in access to medical care, health behaviors (such as smoking and drinking), time preferences, and social status\stress.…”
Section: Background On Domestic Violencementioning
confidence: 99%
“…A large literature shows that those of low socio-economic status are characterized by worse health than their better-off counterparts and that differences in health often originate in childhood and even earlier, in the newborn period (see Case, Paxson and Lubotsky, 2002; Deaton, 2002; Cutler, Deaton and Lleras-Muney, 2006 and references therein). Explanations of the gradient include differences in access to medical care, health behaviors (such as smoking and drinking), time preferences, and social status\stress.…”
Section: Background On Domestic Violencementioning
confidence: 99%
“…A systematic review found 1 While we continue using the expression 'SES' as a comprehensive proxy, we emphasise that the precise choice of SES (i.e. income, education, occupation, or others) may make a great difference both in the assessment of the extent of socio-economic inequalities in health (Wagstaff and Watanabe, 2003) as well as for policy implications (Deaton, 2002). 2 Transitory fluctuations in income may only have a small influence on health (Contoyannis et al, 2004), compared with the strong influence of long term income (Case et al, 2001).…”
Section: Assessing Causalitymentioning
confidence: 99%
“…This discussion is highly policy relevant because, among the components of socioeconomic status (education, income, and occupation), education seems to be the one that -in the long run -appears to be most amenable to public policy interventions. Moreover, as noted by Deaton (2002), it is important to frame social policy in terms of health and wealth simultaneously. Improving one at the expense of the other involves a difficult and probably unnecessary trade-off.…”
Section: Introductionmentioning
confidence: 99%